2017
DOI: 10.1007/s12070-017-1225-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Pterygopalatine Fossa Injection with Adrenaline an Effective Technique for Better Surgical Field in Fess?

Abstract: Functional endoscopic sinus surgery (FESS) is one of most common surgeries in otorhinolaryngology practice. It is done in the narrow confines of the nasal cavity. Bleeding into the surgical field is a major problem faced by endoscopic surgeons. To assess the effectiveness of pterygopalatine fossa infiltration with lignocaine and adrenaline in controlling surgical field bleeding during endoscopic sinus surgery. A randomized blinded study was done among 68 patients who underwent FESS. Infiltration with 2% lignoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Although some have recommended this technique as an effective way of reducing blood loss during surgery, [2][3][4][11][12][13] we could not find any significant difference in bleeding between the study and control sides ( p = 0.49), similar to the results of Kumar et al 14 and Valdes et al 1 In a review paper by Shamil et al, in 2017, of seven articles, only two demonstrated a decrease in blood volume in the surgical field in the study group. 15 In contrast, Hwang and colleagues reviewed five articles, which were in favour of this method; additionally, the authors declared that the concentration of 1:80 000 adrenaline solution had a better result in comparison to 1:100 000.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although some have recommended this technique as an effective way of reducing blood loss during surgery, [2][3][4][11][12][13] we could not find any significant difference in bleeding between the study and control sides ( p = 0.49), similar to the results of Kumar et al 14 and Valdes et al 1 In a review paper by Shamil et al, in 2017, of seven articles, only two demonstrated a decrease in blood volume in the surgical field in the study group. 15 In contrast, Hwang and colleagues reviewed five articles, which were in favour of this method; additionally, the authors declared that the concentration of 1:80 000 adrenaline solution had a better result in comparison to 1:100 000.…”
Section: Discussionsupporting
confidence: 83%
“…Correction of coagulopathies, avoidance of predisposing medications in the pre-operative period, proper patient positioning, anaesthetic protocol, topical vasoconstriction, and some drugs like beta-blockers, tranexamic acid and desmopressin, are some of the preventive measures used to decrease blood in the surgical field. 2,3 There are limitations of beta-blocker usage in some patients (e.g. those with asthma); in addition, reports of blindness after the intranasal injection of vasoconstrictors, and limited accessibility of systemic and topical haemostatic agents, are encountered in some instances.…”
Section: Introductionmentioning
confidence: 99%
“…While in a similar study by R Mathew, 1:80,00 of 2% xylocaine with adrenaline was used, they haven't specified the quantity 1 . In another study by Shenoy VS, 2 ml of 1:80,000 solution of adrenaline with 2% lignocaine 16 . All these studies showed a significant effect of pterygopalatine fossa block in controlling bleeding, corroborating with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery and SPGB through EETA are supported by recent technological advancements, have been increasingly used over the last decade for the treatment of pituitary adenoma. 1,2,[6][7][8][9][10][15][16][17][18][19][20][21][22] The main goal of blood pressure control during ETSS was to achieve a dry surgical field to improve visibility and facilitate the surgical approach without complication. In the current study, the MAP, HR was maintained at target levels, with no significant differences between the two groups but it was non-fluctuated in the SPGB group by adjustment the ventilatory support and balanced anesthesia with no or minimal consumption of hypotensive agents compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…So, the injection of local anesthetic with adrenaline around the sphenopalatine ganglion (SPG) to induce vasoconstriction of the sphenopalatine artery, is widely performed after induction of general anesthesia and before the beginning of surgical procedure. 6,7,8,9,10 The sphenopalatine ganglion (SPG); is a large extracranial and one of four parasympathetic ganglia with multiple neural roots, including autonomic, sensory, and motor. SPG is located in the pterygopalatine fossa, posterior to the middle nasal turbinate under a 1-1.5 mm layer of a mucous membrane, connective tissue and anterior to the pterygoid canal.…”
Section: Introductionmentioning
confidence: 99%